INFLUENCE OF STUDENT BASED FACTORS ON EDUCATIONAL WASTAGE IN PUBLIC SECONDARY SCHOOLS IN MBOONI WEST SUB-COUNTY, MAKUENI COUNTY, KENYA. - Nthangu, Anthony, A.; Kimiti, Richard; Arasa, Robert (Scholarly Research Journal for Interdisciplinary Studies, 2019)
The purpose of this study was to investigate the influence of student based factors on educational wastage in public secondary schools in Mbooni West Sub County, Makueni County. Descriptive survey design was adopted in the study. The target population was 41 public secondary schools. The stratified random sampling technique was used to select a sample of 15 principals, 15 academic deans and 15 form three class teachers giving a total of 45 respondents. Data was collected using questionnaires and document analysis. Quantitative data was analyzed through descriptive statistics using SPSS and qualitative data was analyzed through content analysis. The findings of the study established that student based characteristics significantly influence educational wastage in public secondary schools in Mbooni West Sub-County. The researcher recommends that public secondary schools management in Mbooni West Sub County be sensitized on educational wastage to improve efficiency and guidance and counseling to be strengthened to curb wastage.
Keywords: Educational wastage; Student based factors; Public secondary schools.